Topical capsaicin for chronic neuropathic pain in adults - Derry, S; Lloyd, R; Moore, R; McQuay, H (2009)
Background: Topical creams with capsaicin are used to treat pain from a wide range of chronic conditions including neuropathic pain. Following application to the skin capsaicin causes enhanced sensitivity to noxious stimuli, followed by a period with reduced sensitivity and, after repeated applications, persistent desensitisation. There is uncertainty about the efficacy and tolerability of capsaicin for treating painful chronic neuropathies. Objectives: To review the evidence from controlled trials on the efficacy and tolerability of topically applied capsaicin in chronic neuropathic pain in adults. Search strategy: Cochrane CENTRAL, MEDLINE, EMBASE and Oxford Pain Relief Database, searched in May 2009. Selection criteria: Randomised, double blind, placebo controlled studies of at least six weeks' duration, using topical capsaicin to treat neuropathic pain. Data collection and analysis: Two review authors independently assessed trial quality and validity, and extracted data. Information was extracted on numbers of participants with pain relief (clinical improvement) after at least six weeks, and with local skin reactions, and used to calculate relative risk and numbers needed to treat to benefit (NNT) and harm (NNH). Details of definition of pain relief and specific adverse events were sought. Main results: Six studies (389 participants in total) compared regular application of low dose (0.075%) capsaicin cream with placebo cream; the NNT for any pain relief over six to eight weeks was 6.6 (4.1 to 17). Two studies (709 participants in total) compared a single application of high dose (8%) capsaicin patch with placebo patch; the NNT for ≥ 30% pain relief over twelve weeks was 12 (6.4 to 70). Local skin reactions were more common with capsaicin, usually tolerable, and attenuated with time; the NNH for repeated low dose application was 2.5 (2.1 to 3.1). There were insufficient data to analyse either data set by condition or outcome definition. All studies satisfied minimum criteria for quality and validity, but maintenance of blinding remains a potential problem. Authors' conclusions: Capsaicin, either as repeated application of a low dose (0.075%) cream, or a single application of a high dose (8%) patch may provide a degree of pain relief to some patients with painful neuropathic conditions. Local skin irritation, which is often mild and transient but may lead to withdrawal, is common. Systemic adverse effects are rare. Estimates of benefit and harm are not robust due to limited amounts of data for different neuropathic conditions and inconsistent outcome definition. Copyright © 2009 The Cochrane Collaboration. Published by John Wiley and Sons, Ltd.